2020
DOI: 10.1515/eng-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

The use of simulation modelling for determining the capacity of railway lines in the Czech conditions

Abstract: AbstractSimulation modelling is one way to determine the capacity of railway lines. The specialized software tool OpenTrack was used for simulation. The aim of this paper was to find out whether the OpenTrack simulation software can be used for the calculation of headway, and to compare the results with the methodology of the Railway Infrastructure Administration (SŽDC). Using the software tool, a detailed transport network model can be created including all its important chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…It could be e.g. ATO over ETCS -system controlled by artificial intelligence with possibility, but no necessity of operational staff intervention [6]. The simplified architecture is shown in the Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…It could be e.g. ATO over ETCS -system controlled by artificial intelligence with possibility, but no necessity of operational staff intervention [6]. The simplified architecture is shown in the Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…A model from literature [2] was used for this research. Here, the authors demonstrated the possibility of using the model in the OpenTrack software to simulate the calculation of the headway, which is given by Czech regulations.…”
Section: Methodsmentioning
confidence: 99%
“…The gradual development of the railway network equipped with the ETCS system is moving to the foreground a question about the influence of this system on the throughput of a railway line [1,2]. In addition to the traditional division of the ETCS system into its three basic levels (L1 to L3), based on foreign experience, other implementations of this system are beginning to appear, e.g., with shorter block sections that are about 400 meters long and are largely virtual with stop signs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ExtendSim8 provides very accurate simulation values, and the results of the simulation can be evaluated graphically. The simulation also has its disadvantages, in that it is sensitive to the accuracy of the input data [37,38]. The simulation results will only be as accurate as the data entered into the simulation model.…”
Section: Introductionmentioning
confidence: 99%